2014
DOI: 10.1002/jbmr.2421
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Is a Critical Autocrine/Paracrine Factor for Osteoclast Differentiation

Abstract: Bone metabolism is a vital process that involves resorption by osteoclasts and formation by osteoblasts, which is closely regulated by immune cells. The neuronal guidance protein Netrin-1 regulates immune cell migration and inflammatory reactions, but its role in bone metabolism is unknown. During osteoclast differentiation, osteoclast precursors increase expression of Netrin-1 and its receptor Unc5b. Netrin-1 binds, in an autocrine and paracrine manner, to Unc5b to promote osteoclast differentiation in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 56 publications
2
66
2
Order By: Relevance
“…A previous study also showed enhanced in vitro osteoclastogenesis in netrin 1 knockdown osteoclasts (34). The lack of netrin 1 in osteoclasts may affect the signaling that regulates the intracellular differentiation of these cells (34). However, no enhancement of RANKL-induced osteoclastogenesis by netrin 1 knockdown in MDMs was observed in our experiment (data not shown).…”
Section: Role Of Netrin 1 In Bone Homeostasiscontrasting
confidence: 46%
See 2 more Smart Citations
“…A previous study also showed enhanced in vitro osteoclastogenesis in netrin 1 knockdown osteoclasts (34). The lack of netrin 1 in osteoclasts may affect the signaling that regulates the intracellular differentiation of these cells (34). However, no enhancement of RANKL-induced osteoclastogenesis by netrin 1 knockdown in MDMs was observed in our experiment (data not shown).…”
Section: Role Of Netrin 1 In Bone Homeostasiscontrasting
confidence: 46%
“…A recent study showed that netrin 1 is expressed in murine osteoclasts and stimulates their differentiation in an autocrine fashion (34). However, when we compared these results with osteoblasts and synovial fibroblasts, we found that netrin 1 is barely expressed in osteoclasts at both the mRNA and the protein levels.…”
Section: Role Of Netrin 1 In Bone Homeostasiscontrasting
confidence: 38%
See 1 more Smart Citation
“…It has been reported that Ntn1 is involved in regulating bone remodeling. Mediero et al demonstrated that Ntn1, which is produced by osteoclasts enhanced osteoclast differentiation by an autocrine/paracrine manner and Ntn1 deficient mice have markedly diminished osteoclasts, as well as increased cortical and trabecular bone density and volume compared to wildtype mice, suggesting that Ntn1 is a negative regulator in bone metabolism (11). In contrast, Maruyama et al reported that Ntn1 suppresses osteoclast multinucleation, but not osteoclast differentiation and protected the mice against autoimmune bone destruction in vivo, indicating that Ntn1 is a positive regulator in bone metabolism (12).…”
Section: Discussionmentioning
confidence: 99%
“…Among these netrins, netrin-1 (Ntn1) has involved in cytoskeleton reorganization and in epithelial cell adhesion and migration in lung, mammary gland, and pancreas (8-10). Recent studies showed that Ntn1 plays a crucial role in osteoclast differentiation (11,12). As the function of osteoclasts is regulated by Ntn1, the question whether Ntn1 affects cellular function in osteoblasts has been raised.…”
mentioning
confidence: 99%